Molecular Identification of Species Caused Cutaneous Leishmaniasis in South-ern Zone of Iran - Afshin Barazesh; Mohammad Hossein Motazedian; Moradali Fouladvand; Gholamreza Hatam; Saeed Tajbakhsh; Sepideh Ebrahimi; Danial Purkamal (Tehran University of Medical Sciences, 2018)
Background: Leishmania major and Leishmania tropica are two main species causing cutaneous leishmaniasis (CL) in Iran. Recently, Crithidia spp. has also been reported in the wound of patients with CL. In this study, we determined the species causing CL in the southern of Iran and the role of Crithidia spp. in creating skin ulcers. Methods: In this cross-sectional study from Apr to Sep 2016, 66 patients with CL referred to Diagnostic Lab of Leishmaniasis, Valfajr Health Center, Shiraz, Iran, were selected. After DNA extraction from the Giemsa stained smears, all samples were amplified in two separate steps using specific primers, firstly, to differentiate Leishmania species and then to identify Crithidia spp. Results: Two species L. major and L. tropica were responsible for 60 and 6 cases, respectively. Moreover, in two patients, mixed infection with Crithidia was confirmed. In mix infection cases, the morphology of the cutaneous ulcers was not different from the wounds of other patients. Conclusion: Leishmania major is responsible for the most common CL in southern Iran. In addition, in two patients with L. major and L. tropica, mix infection with Crithidia was confirmed. The potential role of Crithidia as the main factor for CL and the probability of this parasite to have synergistic effects on Leishmania, as a hypothesis, requires more comprehensive researches on the ambiguity of this protozoon.